Knowledge of a Social Profile and its Role in Marketing Practice of Schools in “Knowledge Society” - Roubal, Ondřej (Communication Today, 2025)
Knowledge society faces the challenges to the universalization of education. A changeover from massificationto universalization of education brings new views on the role and functions of education, and of course, on the contents of knowledge mediated by a tertiary education system. The number of university educated students in the Czech Republic is increasing very quickly. The percentage of university graduates on the labour market is growing rapidly. Competitive environment on the Czech labour market is tougher than it used to be. The competition between universities is going up, especially in the private sector of tertiary education. The current number of private universities becomes untenable considering the decreasing number of potential applicants caused by the negative demographic movements of age structure of population. Success in stiff competitive environment of universities means consistent strategic leadership of schools and precise conceptions of marketing campaigns. These campaigns should include marketing statements based on facts, rational arguments and objective information. The useful basis for these statements could be empirical data of social profiles of our own students and competitive students’ population as well. The sociological research of social profiles of graduated students may serve not only as a material for credible and effective promotion of schools, but also as a rational starting point of the increasing educational level of schools.